Numerical studies of electric double layer effect through microchannel flows - Poh, Soon Teong. (2008)
This work serves to perform a numerical analysis with the use of a finite-volume scheme on the liquid flow and heat transfer in microchannels, with streaming potential as the driving force. The concept f electric double layer (EDL) was introduced to explain the microscale deviation.